Pengaruh Penyumbatan Kerak Pada Sistem Injeksi Bahan Bakar Terhadap Daya Motor Induk Kapal - Wibowo, Riyanto (Marine Science and Technology Journal; Vol 2 No 1 (2021): Marine Science and Technology JournalDO - 10.31331/maristec.v2i1.1781, 2021)
Cases of decreased mains motor power often occur on ships, especially ships that are old. However, it is rarely thought that this is caused simply because the carbon crust that clogs the fuel injection system in this case is the nozzle. Blockage of the nozzle crust can be fatal in reducing the power of a ship's motor. Like what happened to the motor of the Kirana II ship, the power of the motor has decreased. As a result, the actual 0.5 mm nozzle hole has been reduced for each nozzle; Nozzle1 0.32mm, nozzle2 0.34mm, nozzle3 0.36mm, nozzle4 0.38mm, nozzle5 0.30mm, nozzle6 0.40mm, nozzle7 0.28mm, nozzle8 0.34mm, so that the motor power has decreased from the previous 4400 HP to 3033.7 HP, this means the motor has a power loss of 1366.3 HP. The shrinkage of the nozzle hole is due to dirt in the form of combustion crust.